Reducing maternal and child oral health disparities in Sub-Saharan Africa through a community-based strategy - Adeniyi, Abiola; Akama, Gladys; Lukandu, Ochiba; Ikemeri, Justus E.; Jumah, Anjellah; Chelagat, Sheilah; Kasuya, Anusu; Ruhl, Laura; Songok, Julia; Christoffersen-Deb, Astrid (Frontiers in Oral Health, 2024)
Oral conditions disproportionately affect mothers and children in Sub-Saharan Africa, due to biological vulnerabilities, a scarcity of oral health workers, deficient preventive strategies, and gender-based barriers to care. The World Health Organization (WHO) recommends integrating oral health into broader health delivery models, to reduce these disparities. We propose integrating preventive oral healthcare into community-based programs to bridge these gaps. We examine integrating preventive oral healthcare into Western Kenya's Chamas for Change (Chamas) community-based program which aims to reduce maternal and child health disparities. Chamas incorporates women's health and microfinance programs best practices to produce a low-cost, community-driven, sustainable, and culturally acceptable health delivery platform. Our strategy is based on the Maternal and Child Oral Health Framework and uses the WHO Basic Package of Oral Care principles. This framework prioritizes community involvement, cultural sensitivity, regular screenings, and seamless integration into general health sessions. We discuss the strengths, weaknesses, opportunities, and threats to enriching Chamas with oral health promotion activities. It is crucial to assess the effectiveness, sustainability, and acceptability of the proposed strategy through implementation and evaluation. Future studies should investigate the long-term impact of integrated oral health models on community health and oral health disparity reduction in Africa.